Gut microbiota and metabolic syndrome - Wang, Peng-Xu; Deng, Xin-Ru; Zhang, Chen-Hong; Yuan, Hui-Juan (Chinese medical journal, 2020)
Metabolic syndrome (MetS) describes a set of risk factors that can eventually lead to the occurrence of cardiovascular and cerebrovascular disease. A detailed understanding of the MetS mechanism will be helpful in developing effective prevention strategies and appropriate intervention tools. In this article, we discuss the relationship between the clinical symptoms of MetS and differences in the gut microbial community compared with healthy individuals, characterized by the proliferation of potentially harmful bacteria and the inhibition of beneficial ones. Interactions between gut microbiota and host metabolism have been shown to be mediated by a number of factors, including inflammation caused by gut barrier defects, short-chain fatty acids metabolism, and bile acid metabolism. However, although we can clearly establish a causal relationship between gut microbial profiles and MetS in animal experiments, the relationship between them is still controversial in humans. Therefore, we need more clinical studies to augment our understanding of how we can manipulate the gut microbiota and address the role of the gut microbiota in the prevention and treatment of MetS.